Visible Range Plasmonic Modes on Topological Insulator Nanostructures - Dubrovkin, Alexander M. (2017)
Phase-resolved real-space imaging of localized plasmons in Bi1.5Sb0.5Te1.8Se1.2 topological insulator nanostructures is performed by scattering-type scanning near-field optical microscopy. Dipolar and higher order surface plasmon modes with well-defined field amplitude and phase profiles are detected in the visible part of the spectrum.